The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

Report of the Presidential Working Party on Education Reform: ​​Transforming education, training and research for sustainable development in Kenya - Government of Kenya (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:4REVBWCX

Education Sector Budget Proposal Report 2023/24 - Government of Kenya (Government of Kenya, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:N7CKV3JH 2405685:NHE2TZSP 4656463:RVPQB2Q4

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8370318 ZenodoArchiveConcept: 8370317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8370318 10.53832/edtechhub.0175 2405685:XRGSHEUJ
Keywords: _r:AddedByZotZen

Learners and Caregivers' Barriers and Attitudes to SMS-based Mobile Learning in Kenya: Key findings from a telephone survey - Jordan, Katy; Damani, Kalifa; Myers, Christina; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7689021 ZenodoArchiveConcept: 7689020 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7689021 10.53832/edtechhub.0162 2405685:FQV2DUEH 2405685:JV87UGDX
Keywords: _r:AddedByZotZen

Collaboration to Realise Kenya’s National Learning Goals through EdTech - Otieno, Jennifer; Omuthe, Ronald; Ampofo, Rudolph (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 10340063 ZenodoArchiveConcept: 10340062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10340063 10.53832/edtechhub.0179 2405685:A76IFCAT
Keywords: _r:AddedByZotZen

Climate Change and Education in Kenya - Fitzpatrick, Rachael; Amenya, Donvan (Education Development Trust, 2023)
What impact does climate change have on education, especially in areas which are vulnerable to climate disasters and extreme weather events? In this report, we explore the impact of climate change on schools and learning in six counties in Kenya (Nairobi, Mombasa, Turkana, Tana River, Kwale and Kilifi).
KerkoCite.ItemAlsoKnownAs: 2339240:D863LELH 2405685:XKNUY5HA

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Stakeholders’ perspectives of enablers and barriers to successfully implementing an integrated early childhood development program in an informal urban settlement in Kenya - Ssewanyana, Derrick; Martin, Marie-Claude; Angwenyi, Vibian; Kabue, Margaret; Proulx, Kerrie; Zhang, Linlin; Malti, Tina; Njoroge, Eunice; Nasambu, Carophine; Marangu, Joyce; Odhiambo, Rachel; Ombech, Eunice; et al. (SAGE Open, 2023)
Integrated early childhood development (ECD) programs boost child health and developmental outcomes. However, the factors contributing to the successful implementation of such programs in informal urban settlements are not well researched. We conducted 14 focus group discussions and 13 key informant interviews with 125 caregivers of children under the age of 5 years and stakeholders, exploring their views on enablers and barriers to implementing an integrated ECD program in an informal settlement in Kenya. Strategic engagement, capacity building, transparency, fair compensation of ECD workforce, communication skills, and the need to tailor ECD programs to local realities were discussed. An equity-focused implementation approach for integrated ECD programs is timely.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/21582440231208986 2339240:AJEW5QXZ 2405685:DKJM4M97

Learners and caregivers barriers and attitudes to SMS-based mobile learning in Kenya - Jordan, Katy; Damani, Kalifa; Myers, Christina; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (African Educational Research Journal, 2023)
The use of mobile phones has been identified as a potential way to bring the benefits of educational technology to a wider audience, including in low-connectivity settings. This is a topic that has received renewed interest recently as a result of the COVID-19 pandemic and school closures. While a number of recent studies have demonstrated good potential for mobile phones and SMS to be used to support learning, there are also questions about how equitable this medium is in practice. We conducted a telephone survey with learners (n = 122) and their caregivers (n = 124) who use M-Shule, an SMS-based educational platform in Kenya, in order to understand their attitudes towards mobile learning, and the benefits and constraints. In particular, we consider whether there are differences in responses according to gender and/or location, to shed light on whether use is equitable. We find that girls and boys face similar barriers to use, and the technology is perceived to be equally beneficial. We identify some areas for potential further support for all learners through mobile learning.
KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.114.23.088 2405685:6BR2KK45

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
ZenodoArchiveID: 10079721 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1000 ZenodoArchiveConcept: 10079720
Keywords: _internal; _r:AddedByMyEducationEvidence

An exploratory investigation into the factors related to EdTech use among Kenyan girls - Watson, Joe; Baier, Jasmin; Mughogho, Winnie; Millrine, Mark (British Journal of Educational Technology, 2023)
This paper contributes to the scarce literature on factors affecting EdTech use in households. These factors were considered through exploratory mixed-methods analyses of cross-sectional data on Kenyan girls and caregivers, captured during the COVID-19 pandemic. Quantitative analysis of the child dataset (n = 544) suggested the importance of both structural factors—such as technology hardware availability—and non-structural factors—including caregiver permission. Findings were supported by a thematic analysis of interview data from girls' caregivers (n = 58), which emphasised the role they play in girls' use of EdTech. Interviews also highlighted numerous caregiver concerns with EdTech, related to the relevance and rigour of educational content, the possibility of children accessing age-inappropriate material and child health (especially eyesight). Policy makers could alleviate these concerns by providing guidance on EdTech use and clearly signalling their approval of verified initiatives. Practitioner notes What is already known about this topic EdTech can benefit girls' education, yet there are various barriers to it being used. Existing research shows clearly that EdTech use can be impeded by structural factors (eg, hardware ownership). However, we find insufficient empirical evidence on the role of non-structural or behavioural factors. What this paper adds This paper addresses this gap, using a mixed-methods approach to explore the influence of 33 different measures (including non-structural factors) that could affect the number of hours girls spend using EdTech at home. Findings from a quantitative sample of girls (n = 544) and a qualitative sample of girls' caregivers (n = 58) highlighted the importance of non-structural factors, especially caregiver permission. The variable most strongly associated with girls' EdTech usage in our selected quantitative model concerned whether this was sanctioned by their caregivers. Our qualitative data suggested why caregiver permission to use EdTech might be withheld: caregivers emphasised perceived concerns about the risks and rigour of EdTech. Implications for practice and/or policy Our findings suggest the viability of policy interventions that provide EdTech guidance to caregivers. Caregivers uncertain about EdTech could be reassured of the appropriateness of verified initiatives, while those already convinced might be aided in their attempts to support EdTech learning. Such guidance could provide a low-cost means of further exploiting the benefits that household EdTech learning can provide.
1 citations (Crossref) [2024-02-28] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13307 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13307 2339240:Q94ZI2GS 2405685:W4VSMH86
Keywords: COVID-19; EdTech; Kenya; caregivers; girls' education; ⛔ No INSPIRE recid found

Low-tech personalised learning to improve girls' education in Kenya. - Jordan, K; Damani, K; Khagame, P; Mongeau, C; Mumbi, A; Myers, C; Njuguna, L; Otieno, J; Zhao, A (EdTech Hub and M-Shule, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:M7HVSHJG 2405685:KN2IBMDV

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2023.102841 2405685:EFV98PTB

Assessment of parent’s engagement in implementation of competency-based curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County, Nithi County, Kenya - Njeru, Atanasia Ikoore; Kirimi, Josephine (European Journal of Education Studies, 2023)
Education is a shared responsibility and all stakeholders need to understand and appreciate what is being done and what is required of them to make meaningful contributions to the process. Because the Competency-Based Curriculum shifted its focus from teaching-centric to collaborative-centered, parents are important stakeholders for its successful implementation. Therefore, empowering and engaging a parent in the learning process is essential to the learner’s growth and development. The study examined parents’ engagement in CBC implementation. This study specifically aimed to determine parents’ engagement in the implementation of Competency-Based Curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County. To get this, the researcher went to private primary schools in Tharaka South Sub County to observe how parents are embracing CBC and randomly selected some parents for interviews, teachers, and head teachers to fill out questionnaires. The study adopted a descriptive survey design where the targeted population was drawn from the 30 private schools in the sub-county. The study targeted 528 respondents. 66 respondents were sampled: 42 parents, 18 teachers and 6 head teachers. Simple random sampling was then used to select the participant. The study conducted a pretest study in 3 private primary schools for the purpose of validating the research instruments. Data was collected using questionnaires for head teachers and teachers and interview schedules for parents. The validity of the research instruments was determined through expert judgment whereas the reliability of the questionnaires was determined through a Cronbach’s alpha coefficient of 0.7982 was obtained. Qualitative data was analyzed thematically whereas quantitative data was summarized using percentages, mean, standard deviation and frequencies were used. This was facilitated by the Statistical Package for Social Sciences (SPSS) Version 21. The study established a significant relationship between the parent’s literacy and the implementation of CBC with a significance value of p=0.000<0.05. The study concluded that the implementation of CBC is greatly challenged by a lack of sensitization on the implementation of the CBC and perceived CBC as expensive, demanding and time-consuming. Thus, recommended that the private schools get more time with their parents to sensitize them on the CBC implementation and get to know their role in the academic performance of their children and also try to change their perception of CBC as expensive, demanding and time-consuming. Article visualizations:
Number: 7 KerkoCite.ItemAlsoKnownAs: 10.46827/ejes.v10i7.4890 2339240:U8V7ZQBP 2405685:6DAPRS4W
Keywords: competency-based curriculum; curriculum implementation; parent’s engagement

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adeniran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (Southern Voice, 2023)
This study examines the adoption of education technology (ed-tech) in primary and secondary education in 10 sub-Saharan African countries: Nigeria, South Africa, Sierra Leone, Uganda, Kenya, Tanzania, Cameroon, Benin, Malawi, and Senegal. The study assesses the development and implementation of ed-tech policies and programmes in the region, exploring how far ed-tech has advanced learning outcomes, improved access, and reduced education inequalities within and between countries in sub-Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 2339240:RUBC88S3 2405685:TE8RFCSM

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.
Accepted: 2023-09-06T13:30:22Z KerkoCite.ItemAlsoKnownAs: 2339240:KW99KLTL 2405685:7V8V344E

Learning Curve: Progress in the Replication Crisis - Angrist, Noam; Cullen, Claire; Ainomugisha, Micheal; Bathena, Sai Pramod; Bergman, Peter; Crossley, Colin; Letsomo, Thato; Matsheng, Moitshepi; Panti, Rene Marlon; Sabarwal, Shwetlena; Sullivan, Tim (AEA Papers and Proceedings, 2023)
We present detailed monitoring data across a five-country randomized trial of phone-based targeted tutoring–one of the largest multicountry replication efforts in education to date. We study an approach shown to work in Botswana and replicated in India, Kenya, Nepal, the Philippines, and Uganda. While the existing literature often finds diminishing effects as proof-of-concept studies are replicated and scaled, we find the opposite: implementation fidelity (the degree of targeted educational instruction) improves across replications and over time. This demonstrates that replication is not intractable; rather, equipped with mechanisms to learn from experience, organizational “learning curves” can enable effective replication and scale-up.
KerkoCite.ItemAlsoKnownAs: 10.1257/pandp.20231009 2405685:48MA4RDL

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Can A/B Testing at Scale Accelerate Learning Outcomes in Low- and Middle-Income Environments? - Friedberg, Aidan (Artificial Intelligence in Education. Posters and Late Breaking Results, Workshops and Tutorials, Industry and Innovation Tracks, Practitioners, Doctoral Consortium and Blue Sky, 2023)
On current trends the world will fail to reach the objectives set in the UN’s Sustainable Development Goals for Education by 2030 or even within the 21st century. Changing this trend will require a significant acceleration in learning outcomes. Digital personalised learning (DPL) tools are a potentially cost-effective intervention that can contribute to this acceleration. In particular, the continuous experimentation afforded by these tools through software A/B testing, has considerable potential to create compounding improvements in learning outcomes. This paper provides an overview of EIDU, an educational platform combining student focused DPL content with digital structured pedagogy programmes in public pre-primary schools in Kenya. Collection of student’s longitudinal unsupervised assessment data at scale creates the possibility of learning outcome focused A/B testing. This is a novel contribution to the development and research field as up until now this type of capability has largely been confined to students in high-income environments.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-36336-8_119 2339240:EWGWHJXK 2339240:SL8MC9DM 2405685:FG4XFKKM 2405685:MYQJA7TD

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

KEY FIGURES: 5th Rwanda Population and Housing Census (PHC) - National Institute of Statistics of Rwanda. (National Institute of Statistics of Rwanda., 2023)
The fifth Population and Housing Census in Rwanda, was conducted in August 2022. The Census operation was coordinated by the National Census Commission. Various census technical and administrative structures have been put in place to ensure a successful census operation.